Tradisi Penyerahan Perabot Rumah Tangga dalam Perkawinan Masyarakat di Kabupaten Bulukumba: Perspektif Hukum Islam - Saputra, Dandi; Cahyani, A. Intan; Kahfi, Ashabul (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
The handover of household furniture in the marriage of the lembanna village community has become a tradition. However, this tradition is a tradition that does not exist in the marriage shari'a in Islam. The main problem in this study is how the Tradition of Handing Over Household Furniture in Marriage of the People of Lembanna Village, Bontobahari District, Bulukumba Regency in the Perspective of Islamic Law. The purpose of this study is to determine the Islamic Legal Perspective on the Tradition of Handing Over Household Furniture in Marriage of the People of Lembanna Village, Bontobahari District, Bulukumba Regency. This research uses a type of field research (field research), with a sociological research approach. The results of this study show that this tradition of handing over household furniture is a must for a groom, even though there is no special request from the bride. Regarding luggage in Islam is the responsibility of the prospective groom, therefore the tradition in Lembanna Village, Bontobahari District, Bulukumba Regency does not contradict Islamic law at all.